New Worm on the Block: Planarians in (Neuro)Toxicology. Issue 12 (26th December 2022) - Ireland, Danielle; Collins, Eva‐Maria S.
Abstract: Traditional mammalian testing is too time‐ and cost‐intensive to keep up with the large number of environmental chemicals needing assessment. This has led to a dearth of information about the potential adverse effects of these chemicals, especially on the developing brain. Thus, there is an urgent need for rapid and cost‐effective neurotoxicity and developmental neurotoxicity testing. Because of the complexity of the brain, metabolically competent organismal models are necessary to understand the effects of chemicals on nervous system development and function on a systems level. In this overview, we showcase asexual freshwater planarians as an alternative invertebrate ("non‐animal") organismal model for neurotoxicology research. Planarians have long been used to study the effects of chemicals on regeneration and behavior. But they have only recently moved back into the spotlight because modern molecular and computational approaches now enable quantitative high‐content and high‐throughput toxicity studies. Here, we present a short history of the use of planarians in toxicology research, highlight current techniques to measure toxicity qualitatively and quantitatively in planarians, and discuss how to further promote this non‐animal organismal system into mainstream toxicology research. The articles in this collection will help work towards this goal by providing detailed protocols that can be adopted by the community to standardize planarian toxicity testing. © 2022 Wiley Periodicals LLC.